Psychoreligius Experiences to Control Emotion in Patientswith the Risk of Violent Behavior at Central Java, Indonesia - PH, Livana; Dawood, Eman (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Implementation strategies (SP) are carried out as a means of evaluation, in other words strategies used to carry out self-introspection in order to demand that oneself achieve better goals and results and minimize the possibility of deficiencies or failures.. The research aims to determine psychoreligious experiences in controlling emotions in patients at risk of violent behavior. The research used was descriptive qualitative, with data analysis using the Colaizzi method, with five participants. The inclusion criteria for participants were inpatients with a nursing diagnosis of risk of violent behavior and cooperative patients. This research was conducted at RSJD Dr. Amino Gondohutomo, Central Java Province. The results of interviews related to psychoreligious experiences in controlling emotions in patients at risk of violent behavior, all participants admitted that psychoreligious practices: prayer, dhikr and supplication were able to reduce emotions. Participants stated that they felt calmer when they were close to their God. These psychoreligious activities can be applied into daily activities for patients especially with violent behavior, this method can also be applied in daily life to feel calmer and able to live life well again.